Medulloblastoma therapy: Consensus treatment recommendations from SIOP-Europe and the European Reference Network - S. Bailey; S. Jacobs; M. Kourti; M. Massimino; N. Andre; F. Doz; C. Dufour; S. Vennarini; L. Padovani; K. Aquilina; U. Thomale; A. Joshi; et al. (EJC Paediatric Oncology)
The treatment of medulloblastoma has evolved considerably over the last 10 years. Treatment intensity is now stratified within clinical trials, using risk-associated clinical features and molecular biomarkers, aimed at maximising cure rates whilst minimising long-term disease and therapy-associated side-effects. In Europe, we have developed a long-term strategy of using randomised trials to test stratified treatments across all medulloblastoma disease demographics, and to investigate further stratification using biological analysis of the samples collected. Importantly, care must be taken not to adopt experimental arms from trial protocols into routine practice, prior to trials’ results being available. Moreover, there are time periods when trials are not open to recruitment for all the various risk-groups. These guidelines, developed under the auspices of SIOP-Europe and the European Reference Network for Paediatric Oncology, ERN PaedCan, review recent and current trials, alongside the literature, to provide evidence-based guidance for the contemporary therapy of medulloblastoma.